2022
DOI: 10.1186/s40792-022-01461-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of radical resection for brain metastases of pancreatic cancer after curative chemotherapy for para-aortic lymph node metastases

Abstract: Background The incidence of brain metastasis of pancreatic cancer has been reported to be approximately 0.3%. The blood–brain barrier of the central nervous system restricts the transfer of substances, including chemotherapeutic agents, from the bloodstream. It is hypothesized that brain metastasis may occur despite successful chemotherapy for the primary tumor. Herein, we report a case of brain metastases of pancreatic cancer that occurred after chemotherapy and discuss relevant literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on our literature review, 24 articles were found, including 61 patients ( Supplementary Table S1 , Supplementary Materials ) ( 15 38 ). The pooled patient characteristics are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our literature review, 24 articles were found, including 61 patients ( Supplementary Table S1 , Supplementary Materials ) ( 15 38 ). The pooled patient characteristics are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…( 29 ). One additional patient displayed a somatic BRCA2 mutation in both the primary pancreatic tumor and BM ( 38 ). At initial diagnosis, 25 patients (41%) had localized PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular profiling of tumour may provide the answer to why certain patients are more likely to develop brain metastasis. Two recent case series and case report had identified possible link between germline BRCA1/2 mutations and development of brain metastasis in patients with pancreatic adenocarcinoma 6 13. While BRCA gene mutation only accounts for 4%–7% of patients with pancreatic adenocarcinoma, studies had shown that treatment with platinum-based chemotherapy and poly-ADP ribose polymerase inhibitor such as olaparib in this population may prolong overall survival and progression-free survival, respectively 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases from hepatocellular carcinoma (HCC), cholangiocarcinoma (CCC), and pancreatic carcinoma (PCC) are very rare, with incidence rates of 0.2-2.2%, 0.5-1.4%, and 0.3-0.6%, respectively [1][2][3]. The onset of brain metastases from these primary malignancies often represents a late manifestation of the primary disease.…”
Section: Introductionmentioning
confidence: 99%